Pedagogical knowledge in Chile: a contradictory context: un contexto contradictorio (Educational Perspectives Magazine (REPED), 2023)
This paper is about pedagogical knowledge in Chile and the contextual aspects that influence it. Due to the academic dimensión of pedagogical knowledge, the study analyzes the impact of improvements in initial teacher training as well as of the development of educational research. Regarding teachers’ professional knowledge, the recent changes in the evolution of the teaching profession are analyzed. The paper States contradictory aspects of the context. There are tendencies pointing towards the weakening of pedagogical knowledge and its illegitimacy. Others point towards its strengthening.
Keywords: Pedagogical Knowledge, Educational Policies, Teacher’s Profession, Educational Reform.